A novel allele, HLA‐DPB1*296:01, identified by sequence‐based typing in a Thai bone marrow donor. Issue 6 (27th October 2014) - Presciuttini, S.; Sciarrino, R.; Fornaciari, S.; Mariotti, M. L.; Scatena, F.; Curcio, M.
<x xml:space="preserve">Abstract</x> A novel HLA‐DPB1 allele, named DPB1*296:01, was identified in the Thai mother of a hematologic patient.